Shortening the interval between the first and the second dose of vancomycin facilitates rapid achievement of the target AUC without increasing the risk of acute kidney injury, provided the AUC on the second day is appropriately controlled: a multicenter retrospective study - Tomoyuki Ishigo; Ayako Suzuki; Yuta Ibe; Satoshi Fujii; Masahide Fukudo; Hiroaki Yoshida; Hiroaki Tanaka; Hisato Fujihara; Fumihiro Yamaguchi; Fumiya Ebihara; Takumi Maruyama; Yukihiro Hamada; et al. (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background The impact of shortening or extending a vancomycin dosing interval on early attainment of target blood levels and acute kidney injury (AKI) remains unclear. We investigated the relationship between the interval of the first and second doses of vancomycin and early area under the concentration-time curve (AUC) and AKI. Methods Patients (≥ 18 years) who started vancomycin and had trough/peak blood samples were included. The definition of shortened interval as the first and second doses of vancomycin was < 12 h. The cumulative incidence of AKI within 21 days was compared using the shortened interval and AUC on day 1 and 2. Results Among 668 patients (median age 69 [interquartile range (IQR): 57, 78] years, 40% female), the proportion achieving an AUC ≥ 400 µg·h/mL on day 1 was significantly higher in the shortened-interval group (82% vs. 50%; p < 0.001). Multivariate analysis revealed no association between a shortened interval (hazards ratio [HR], 1.10 [95% confidence interval (CI), 0.63–1.91]; p = 0.750) or an AUC > 600 µg·h/mL on day 1 alone (HR, 2.17 [95% CI, 0.64–7.42]; p = 0.220) and AKI onset. However, an AUC > 600 µg·h/mL on day 2 alone (HR, 2.92 [95% CI, 1.45–5.87]; p = 0.003) or on both days (HR, 11.18 [95% CI, 5.07–24.67]; p < 0.001) was significantly associated with increased AKI risk. Conclusions Shortening the dosing interval facilitates early achievement of target AUC without increasing AKI risk, provided AUC on day 2 is appropriately controlled.